Educational Assortative Mating and Harsh Parenting in Sub-Saharan Africa - Luca Maria Pesando; Elisabetta De Cao; Giulia La Mattina; Alberto Ciancio (Institute of Labor Economics (IZA), 2023)
Leveraging underused information on child discipline methods, this study explores the relationship between parental educational similarity and violent childrearing practices, testing a new potential pathway through which parental educational similarity may relate to child outcomes. The study uses data from Multiple Indicator Cluster Surveys (MICS) and Demographic and Health Surveys (DHS) covering 27 sub-Saharan African (SSA) countries. Results suggest that educationally similar couples are less likely to adopt violent childrearing practices relative to educationally dissimilar ones, with differences by age of the child, yet less so by sex and birth order. Homogamous couples where both partners share high levels of education are also less (more) likely to adopt physically violent (non-violent) practices relative to homogamous couples with low levels of education. Relationships are stronger in countries characterized by higher GDP per capita, Human Development Index, and female education, yet also in countries with higher income and gender inequalities. Besides stressing the importance of female education, these findings underscore the key role of status concordance vs discordance in SSA partnerships. Tested micro-level mechanisms and country-level moderators only weakly explain result heterogeneity, calling for more research on the topic.
Keywords: I21; J12; J13; O12; O15; O57; 330; education; assortative mating; child discipline; parenting; status consistency; sub-Saharan Africa